Strontium isotope stratigraphy: LOWESS version 3: Best fit to the marine Sr-isotope curve for 0-509 Ma and accompanying look-up table for deriving numerical age - McArthur, JM; Howarth, RJ; Bailey, TR (UNIV CHICAGO PRESS, 2001)
An improved and updated version of the statistical LOWESS fit to the marine Sr-87/Sr-86 record and a revised look-up table (V3: 10/99; available from j. mcarthur@ucl.ac.uk) based upon it enables straightforward conversion of Sr-87/Sr-86 to numerical age, and vice versa, for use in strontium isotope stratigraphy (SIS). The table includes 95% confidence intervals on predictions of numerical age from Sr-87/Sr-86. This version includes the Triassic and Paleozoic record (0-509 Ma) omitted from previous versions because of the paucity of adequate data at the time of preparation. We highlight differences between the previous versions of the table and the current version and discuss some aspects of the Sr-87/Sr-86 record that may have geological significance. We give examples of how the table can be used and where it has proven useful.